Penanaman Nilai Karakter Siswa dengan Peduli Lingkungan di Sekolah Dasar - Lu'luil Maknun; Dinda Aisyah (Universitas Sarjanawiyata Tamansiswa, 2023)
Character is the nature of a person in the form of character, psychological traits, personality, character and behavior in everyday life. Instilling character values ​​is very important to be instilled from an early age. School is one of the right places in instilling character values ​​for children. Routine activities to form student character values ​​are needed with daily, weekly and occasional activities. Implementing an environmental care system, schools can accustom students to care for their surroundings and always maintain cleanliness. As for the purpose of the formation of this article, it is hoped that the character values ​​of students are truly embedded with environmental care that is implemented in schools through picket programs in class, placing trash cans on each side of the school, as well as joint tree planting activities. This study uses a qualitative descriptive approach, which collects data from existing journal articles, then analyzes them, and then draws conclusions.